A Comprehensive Review of Moving Bed Biofilm Reactor for Different Wastewater Treatment and Reuse (Eurasian Journal of Engineering and Technology, 2023)
This review includes some previous studies applied to MBBR in the treatment of sewage water in general, with a mention of the results reached by the researchers, All studies proved the efficiency of MBBR by removing the tested parameters, including COD, BOD, NH4, NO3, NO2, TN, and TP, as well as for bacteria such as total bacteria, coliform bacteria, and fecal bacteria, whether it was used as a primary or additional treatment unit, so this technology is considered one of the most promising technologies. And the modern one that must be focused on studying.